The essential Elizabeth Stone : a novel - Banash, Jennifer (Lake Union Publishing, 2024)
"Her mother let her believe a lie. She's finally ready to learn the truth. For more than thirty years, Elizabeth Stone has been an irreplaceable fixture in homes around the world, a food and lifestyle icon with a brand as warm and inviting as New England brown bread. Until, after her sudden passing, she leaves her legacy and her multimillion-dollar empire to her daughter Juliet, who is expected to step seamlessly into her shoes. Juliet finds herself at both a personal and professional crossroads in her life, fearing she won't be good enough to maintain the image and brand of a woman she adored. With the company in financial trouble, Juliet is urged to write the definitive biography of her mother--self-made entrepreneur, pefect mom, and homespun everywoman whose own childhood in Maine was filled with comfort food and simple elegance. But other than what little Juliet has been told, she doesn't know much about her mother's past. The truth is, no one does. As she digs through her mother's possessions, tracking down those who knew her, Juliet is stunned to uncover a lifetime of secrets and lies. As she uncovers the truth, she is forced to reckon with her grief over missing someone she isn't sure she ever really knew. Faced with decisions about the fate of her mother's empire, as well as Juliet's own marriage and future, she will first have to answer the question on everyone's mind--who was Elizabeth Stone?" --